An integrated belowground trait‐based understanding of nitrogen‐driven plant diversity loss. (14th March 2022) - Tian, Qiuying; Lu, Peng; Zhai, Xiufeng; Zhang, Ruifang; Zheng, Yao; Wang, Hong; Nie, Bao; Bai, Wenming; Niu, Shuli; Shi, Peili; Yang, Yuanhe; Li, Kaihui; et al.
Abstract: Belowground plant traits play important roles in plant diversity loss driven by atmospheric nitrogen (N) deposition. However, the way N enrichment shapes plant microhabitats by patterning belowground traits and finally determines aboveground responses is poorly understood. Here, we investigated the rhizosheath trait of 74 plant species in seven N‐addition simulation experiments across multiple grassland ecosystems in China. We found that rhizosheath formation differed among plant functional groups and contributed to changes in plant community composition induced by N enrichment. Compared with forb species, grass and sedge species exhibited distinct rhizosheaths; moreover, grasses and sedges expanded their rhizosheaths with increasing N‐addition rate which allowed them to colonize belowground habitats. Grasses also shaped a different microenvironment around their roots compared with forbs by affecting the physicochemical, biological, and stress‐avoiding properties of their rhizosphere soil. Rhizosheaths act as a "biofilm‐like shield" by the accumulation of protective compounds, carboxylic anions and polysaccharides, determined by both plants and microorganisms. This enhanced the tolerance of grasses and sedges to stresses induced by N enrichment. Conversely, forbs lacked the protective rhizosheaths which renders their roots sensitive to stresses induced by N enrichment, thus contributing to their disappearance under N‐enriched conditions. This study uncovers the processes by which belowground facilitation and trait matching affect aboveground responses under conditions of N enrichment, which advances our mechanistic understanding of the contribution of competitive exclusion and environmental tolerance to plant diversity loss caused by N deposition. Abstract : Atmospheric nitrogen (N) deposition drives plant diversity loss across different grasslands worldwide. The rhizosheath, as an integrated belowground trait determined aboveground responses to N enrichment by shaping soil properties in rhizosphere microhabitats. Grasses and sedges established an ideal microhabitat by forming and expanding rhizosheaths, thus allowing them to survive in stresses caused by N enrichment, while forbs lacked the belowground facilitation and trait matching, driving them loss from the community. These findings enhance our mechanistic understanding of N‐induced community composition changes.